Electromyographycal findings in human chronic Chaga's disease - M. A. Pagano; G. G. Aristimuño; Susana Basso; A. Colombi; R. E. P. Sica (Arquivos de Neuro-Psiquiatria)
An electromyographical investigation of 80 patients with chronic Chagas' disease was made. It was found that 79% of the studied patients had EMG manifestations of old and chronic denervation of the upper and lower limbs without clinical features of nervous system involvement.